Socialization of Probiotic Propagation for Fish Farming in Tengket Village, Arosbaya, Bangkalan - Abdus Salam Junaedi; Muhammad Zainuri; Alfan Biroli; Sulistina Marliantari; Revi Putri Dwi Anjani; Firdha Maulidyah Pahlevi; Lutfia Ardita Mayra Putri Asrudi; Khoirun Nisa' (STAI Nurul Islam Mojokerto, 2025)
Probiotic propagation is a process to enrich the number of probiotic cells through culture. Probiotics are good microorganisms that can live in the digestive system. Fish probiotics can be beneficial for fish because they help stabilize immunity and support fish growth. Probiotics help suppress the growth of pathogenic bacteria in fish farming. This socialization was carried out in Tengket village, Arosbaya District, Bangkalan. The aim of this activity is to make it easier for cultivators to obtain fish probiotics and minimize spending money on fish probiotics. Propagation of probiotics can be done by making a carrier media (3% molasses) which is mixed with probiotics using a ratio of 1:9 (probiotics: carrier media). Probiotic propagation is said to be successful if there is a change in color and there is sediment at the bottom of the container. Probiotics have benefits for fish farming to improve water quality, improve fish health, suppress pathogenic bacteria and feed efficiency. Another advantage of fish probiotics is that they can regulate the number of bacteria in the fish's digestive tract and produce lactic acid, as well as increasing the effectiveness of enzymes and feed digestibility.